Obtenção de monoésteres graxos a partir do óleo de pinhão manso (Jatrofa curcas L.) por transesterificação e esterificação simultâneas - Salviato, Aroldo (2012)
Over the last few years the preoccupation with the environment where we live, in the light of the scientific community, has raised a debate on global warming, climate changes, shortage of fuel and even discussions about the competition between the crops which are aimed at human food and their utilization as a source of energy. Taking into account all these factors, this work aimed at working with a plant which fits positively in all above aspects: Jatrofha curcas L., commonly known in Brazil as Physic nut, whose oil features in its composition in fatty acid the predominance of oleic and linoleic acid. As acid catalyst esterification can be a process to obtain esters from raw materials with acidity above the levels indicated to transesterification, such process was used in this present work. Therefore, this is a relatively new method and reports on its utilization for the production of biodiesel are still scarce in the published literature. Thus, the physic nut oil was extracted by mechanical press; it presented acidity 12.58% (mg KOH/g). It was used ethanol due to its utilization in Brazil, its renewable and environmentally beneficial nature besides its low toxicity. Sulfuric and hydrochloric acid were used as catalyst. It was found that the great concentration of the oil acidity of the jatrofha curcas is in its peel. The solvent extraction provided yield of 65% in oil against 26% obtained by mechanical extraction of the grains in pre-heated press. The acid esterification, in single step, occurred in closed reactor in batch system. The temperature of 100 °C has shown to be the most suitable and it presented the double of the esters yields if compared to the hydrochloric acid. The amount of 1% of sulfuric acid has provided the highest yields in ethyl esters. Furthermore, ethanol utilization as an esterification agent led to superior yields than methanol utilization. The molar ratio of alcohol: oil (20:1) was considered the most appropriate to the esterification reaction. It was found that to molar ratios superior to that, the yield in ester presented a significant drop. It was also found that water is a decisive parameter to the esterification since it influences negatively the yields. This was stressed by using ethanol 95% m/m. The transfer is minimal above 400 rpm. The results also showed that pressure hasA significant role the simultaneous esterification and transesterification reactions. With pressures higher tham 300 psi, no significant variation in the yield of ester was observed when compared to the 85% value obtained with the use of only 40 psi pressure in the reactor (autogenous pressure).